2019
DOI: 10.21147/j.issn.1000-9604.2019.01.10
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcomes of diffuse large B-cell lymphoma based on nodal or extranodal primary sites of origin: Analysis of 1,085 WHO classified cases in a single institution in China

Abstract: ObjectiveTo explore the clinicobiologic features and outcomes of diffuse large B-cell lymphoma (DLBCL) patients in China according to the primary site.MethodsA total of 1,085 patients diagnosed with DLBCL in National Cancer Center/Cancer Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College during a 6-year period were enrolled. Their clinical characteristics and outcomes were analyzed according to the primary site.ResultsIn the 1,085 patients, 679 (62.6%) cases were nodal DLBCL (N-DLBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 27 publications
5
67
1
2
Order By: Relevance
“…Our previous studies suggest that the prognosis of EN-DLBCL is worse compared with that of N-DLBCL. 10 The 5-year OS rates for patients with N-DLBCL and EN-DLBCL receiving R-CHOP chemotherapy were 65.5% and 56.9%, and the 5-year PFS were 57.0% and 49.0%,respectively. Primary gastric and intestinal DLBCL displayed a different biological behavior and various patterns of antigen expression, but the standard chemotherapy remains the same with that for other N-DLBCLs.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our previous studies suggest that the prognosis of EN-DLBCL is worse compared with that of N-DLBCL. 10 The 5-year OS rates for patients with N-DLBCL and EN-DLBCL receiving R-CHOP chemotherapy were 65.5% and 56.9%, and the 5-year PFS were 57.0% and 49.0%,respectively. Primary gastric and intestinal DLBCL displayed a different biological behavior and various patterns of antigen expression, but the standard chemotherapy remains the same with that for other N-DLBCLs.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, patients with EN-DLBCL appear to have a poorer prognosis compared with those with N-DLBCL. 10 The stomach and intestine are the most common extranodal organs affected by lymphoma. The incidence of primary gastrointestinal (GI) lymphoma is about 30-50% among all NHL cases.…”
Section: Introductionmentioning
confidence: 99%
“…Tumors without such genetic immunoevasion strategies are likely highly immunogenic and must escape from T cell pressure in other ways -their frequent development in extranodal (and often immune privileged) sites is well established (Bruno et al, 2014;Kraan et al, 2013;Shi et al, 2019). Together, these findings might help explain the disappointing clinical outcomes in single-agent immune checkpoint blockade trials for DLBCL (Ansell et al, 2019;Lesokhin et al, 2016) and indicate that NK-mediated or CAR-T immunotherapies may be better suited for ABC DLBCL immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed this demographic feature in the present study. More and more studies showed that primary GI DLBCL had different clinical characteristics and treatment outcomes from nodal DLBCL ( 13 15 ). Some new prognostic evaluation systems are needed to identify high-risk patients.…”
Section: Discussionmentioning
confidence: 99%